Administração experimental de esteróide anabólico androgênico e álcool causa alterações histológicas e morfométricas nos ovários e útero de ratas adultas - Camargo, Isabel Cristina Cherici [UNESP]; de Genova, Tatiana Cristina [UNESP]; de Pontes Machado, Marcela Cristina [UNESP]; Frei, Fernando [UNESP]; Paccola Mesquita, Suzana de Fatima (Universidade Federal de Uberlândia (UFU), 2011)
Abusive and indiscriminate use of androgenic anabolic steroid is an usual practice among youth and adults of both sex. Usually these substances were utilized simultaneously with others drugs, licit or not, that causes damage to health. The purpose of study was to evaluate the influence of experimental administration of nandrolone decanoate steroid (ND), associated or not to alcohol, in the ovaries and uterus of adult rats. Females with regular estrous cycle (n = 20), were distributed in the groups: a) control (physiological solution); b) ND (7.5 mg/kg BW; intraperitoneal); c) alcohol (0.2 mL/100g BW; oral); d) ND + AL. The teatments were realized by single dose per week, during twelve consecutive weeks. The ovaries of rats in the groups ND, AL and ND + AL presented intense follicular atresia and decrease in the number of antral follicles and corpora lutea. None treatment did affect ovarian weight, but uterine weight was increase (p<0.05) in the ND + AL group. There were alterations in the uterine histology and morphometry at function of each treatment. Isolated or simultaneous use of anabolic steroid and alcohol promotes ovarian and uterine toxicity in adult female rats.

O uso abusivo e indiscriminado de esteróides anabólicos androgênicos é uma prática comum entre jovens e adultos de ambos os sexos. Geralmente estas substâncias são utilizadas simultaneamente com outras drogas, lícitas ou não, que causam prejuízos à saúde. O objetivo do estudo foi avaliar a influência da administração experimental do esteróide decanoato de nandrolona (DN), associado ou não ao álcool, nos ovários e útero de ratas adultas. Fêmeas com ciclo estral regular (n=20), foram distribuídas nos grupos: a) controle ( solução fisiológica); b) DN (7,5 mg/kg de peso corpóreo; intraperitoneal); c) álcool (AL; 0,2 mL/100g de peso corpóreo; oral); d) DN + AL. Os tratamentos foram realizados através de uma única dose por semana, durante doze semanas consecutivas. Verificou-se que os tratamentos experimentais promoveram alterações no ciclo sexual, na histologia ovariana e uterina, na quantificação folicular e nos parâmetros morfométricos do útero, sendo estes efeitos marcantes nos grupos androgenizados DN e DN + AL. Concluiu-se que o uso isolado ou simultâneo de esteróide anabólico e álcool promovem toxicidade ovariana e uterina em ratas adultas.
Experimental administration of anabolic androgenic steroid and alcohol causes histological and morphometrical alterations in the ovaries and uterus of adult rats
Keywords: Anabolic steroid; Alcohol; Histomorphometry; Ovaries; Uterus; Rats